RETRACTED: Rheological properties of wheat dough with the addition of green buckwheat flour - Gur’ev Sergey; Ivanova Vera; Korovyansky Vyacheslav; Novichenko Alexander; Kostin Ilia (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001